Surface Independent Factor XI Activation by Thrombin in the Presence of High Molecular Weight Kininogen - von dem Borne, Peter A Kr; Koppelman, Stefan J; Bouma, Bonno N; Meijers, Joost C M (Thrombosis and Haemostasis, 1994)
A deficiency of one of the proteins of the contact system of blood coagulation does not result in a bleeding disorder. For this reason activation of blood coagulation via this system is believed to be an in vitro artefact. However, patients deficient in factor XI do suffer from variable bleeding abnormalities. Recently, an alternative pathway for factor XI activation has been described. Factor XI was found to be activated by thrombin in the presence of dextran sulfate as a surface. However, high molecular weight kininogen (HK), to which factor XI is bound in plasma, and fibrinogen were shown to block this activation suggesting it to be an in vitro phenomenon. We investigated the thrombin-mediated factor XI activation using an amplified detection system consisting of factors IX, VIII and X, which was shown to be very sensitive for factor XIa activity. This assay is approximately 4 to 5 orders of magnitude more sensitive than the normal factor XIa activity assay using a chromogenic substrate. With this assay we found that factor XI activation by thrombin could take place in the absence of dextran sulfate. The initial activation rate was approximately 0.3 pM/min (using 25 nM factor XI and 10 nM thrombin). The presence of dextran sulfate enhanced this rate about 8500-fold. A very rapid and complete factor X activation was observed in the presence of dextran sulfate. Although only minute amounts of factor XIa were formed in the absence of dextran sulfate, significant activation of factor X was detected in the amplification assay within a few minutes. HK inhibited the activation of factor XI by thrombin strongly in the presence, yet only slightly in the absence of dextran sulfate (26 and 1.2 times, respectively). Despite the strong inhibition of HK on the activation of factor XI by thrombin in the presence of dextran sulfate, HK had only a minor effect on the factor Xa generation.We conclude that activation of factor XI by thrombin can take place regardless of the presence of a surface or HK. This activation might therefore be physiologically relevant. The inhibitory effect of HK on the thrombin-mediated factor XI activation is largely dextran sulfate dependent. Due to the amplification in the intrinsic system, trace amounts of factor XIa might generate physiological sufficient amounts of factor Xa for an adequate haemostatic response.